Nutritional Strategies to Combat Type 2 Diabetes in Aging Adults: The Importance of Protein - Beaudry, Kayleigh M.; Devries, Michaela C. (Frontiers in Nutrition, 2019)
The prevalence of pre-diabetes (PD) and type II diabetes (T2D) has risen dramatically in recent years affecting an estimated 422 million adults worldwide. The risk of T2D increases with age, with the sharpest rise in diagnosis occurring after age 40. With age, there is also a progressive decline in muscle mass starting after the age of 30. The decline in muscle mass, strength and function due to aging is termed sarcopenia and immediately precedes the sharp rise in T2D. Muscle mass is the largest storage depot for glucose; thus, the loss of muscle mass can further influence glycemic control in older adults. Furthermore, in the insulin resistant state the rate of muscle mass loss is accelerated, indicating that the risk of sarcopenia is greater in those who are insulin resistant. Given the relationship between muscle mass and insulin sensitivity, it is logical to suggest that T2D and sarcopenia are highly related metabolic disorders and that interventions that can improve one may improve the other as well. It has been well established that the loss of muscle mass in aging adults can be attenuated by increased protein intake and resistance exercise. The current recommended dietary allowance for protein consumption is set at 0.8 g/kg/d, but this is based on studies using young healthy men as participants and may not be sufficient for older adults. Protein intakes of 1.0-1.5 g/kg/d in older adults have been recommended for older adults to attenuate declines in muscle mass and function. Protein intakes in this range are also able to induce improvements in glycemic control in this population. The purpose of this review is to discuss the role of protein to attenuate declines in muscle mass and insulin sensitivity to prevent and manage T2D in aging adults. Furthermore, we will also discuss how the combination of exercise, both resistance and aerobic, and protein can have synergistic effects to prevent the development of T2D.